O objeto matemático triângulo em teoremas de Regiomontanus: um estudo de suas demonstrações mediado pelo Geogebra - Mod, Luiz Felipe Araujo (2016)
Abstract: This Master’s research aims to investigate Regiomontanus’ theorems about triangles with the use of the software GeoGebra. Regiomontanus (1436-1476) was a mathematician whose production contributed especially in the development of trigonometry with the work De Triangulis Omnimodis Libri Quinque, published in 1533 and that is the focus of this research. In the Book I of his work, there are theorems whose demonstrations involve constructions of triangles met some given conditions. Demonstrations of some of these theorems are analyzed by the mediation of the dynamic movements of GeoGebra in view of the functions of the demonstration according to Villiers. There is the need to scroll through the different roles of the demonstration and the importance of the use of GeoGebra as an instrument of investigation, in which it is possible to identify that some possibilities are not included in the Regiomontanus’ demonstrations. The survey, in its development, also indicates possibilities of how a legacy of the History of Mathematics can become a research activity in the classroom